The Trend of â€œIndependent Learning Independent Campusâ€: Teaching Model of Islamic Education through bibliometrics mapping in 2021-2022 - Elihami Elihami; Mohd. Melbourne (Yayasan Keluarga Guru Mandiri, 2022)
This research explained of the trend of â€œIndependent Learning Independent Campusâ€ by using bibliometricsâ€™ mapping in 2010-2021. This study aims to analyze studentsâ€™ perception of the technical, process and evaluation learning of the Independent Learning-Independent Campus. This study is a descriptive with a quantitative approach. The research method used qualitative research. The research method is qualitative approach through VOS viewer. The object of the research were students of Universitas Muhammadiyah Enrekang who participated. The instrument used is in the form of a questionnaire distributed via website. The results obtained from this study are: 1) Studentsâ€™ perception of technical indicators in MBKM learning are positive; they donâ€™t experience signal problems and can access MBKM learning easily; 2) Studentsâ€™ perception of learning process indicators in MBKM learning on average are positive; students can understand MBKM learning materials through discussions and communication between lecturers and students goes well; 3) Studentsâ€™ perception of evaluation indicators in MBKM learning on average are positive; students can do midterm and final exam well independently and students are satisfied with the implementation of MBKM learning so they are interested in following it again in the next semester, but students feel that MBKM learning is not optimal because it is done online.